The maritime world of early modern Britain - Blakemore, Richard, 1987-; Davey, James (Lecturer in naval and maritime history) (Amsterdam : Amsterdam University Press, 2020)
Britain's emergence as one of Europe's major maritime powers has all too frequently been subsumed by nationalistic narratives that focus on operations and technology. This volume, by contrast, offers a daring new take on Britain's maritime past. It brings together scholars from a range of disciplines to explore the manifold ways in which the sea shaped British history, demonstrating the number of approaches that now have a stake in defining the discipline of maritime history. The chapters analyse the economic, social, and cultural contexts in which English maritime endeavour existed, as well as discussing representations of the sea. The contributors show how people from across the British Isles increasingly engaged with the maritime world, whether through their own lived experiences or through material culture. The volume also includes essays that investigate encounters between English voyagers and Indigenous peoples in Africa, and the intellectual foundations of imperial ambition.
Introduction / Richard J. Blakemore, James Davey -- 1. The Minion and Its Travels: Sailing to Guinea in the Sixteenth Century / Bernhard Klein -- 2. Commanding the World Itself : Sir Walter Ralegh, La Popelinière, and the Huguenot Influence on Early English Sea Power / Alan James -- 3. An Investigation of the Size and Geographical Distribution of the English, Welsh, and Channel Islands Merchant Fleet: A Case Study of 1571-72 / Craig L. Lambert, Gary P. Baker -- 4. An Evaluation of Scottish Trade with Iberia during the Anglo-Spanish War, 1585-1604 / Claire McLoughlin -- 5. Performing 'Water' Ralegh : The Cultural Politics of Sea Captains in Late Elizabethan and Jacobean Drama / Claire Jowitt -- 6. 'Wicked Actions Merit Fearful Judgments' : Capital Trials aboard the Early East India Company Voyages / Cheryl Fury -- 7. 'A water bawdy house': Women and the Navy in the British Civil Wars / Elaine Murphy -- 8. 'Thy sceptre to a trident change / And straight , unruly seas thou canst command': Contemporary Representations of King Charles I and the Ship Money Fleets within the Cultural Imagination of Caroline England / Rebecca A. Bailey -- 9. 'Proud Symbols of the Prospering Rural Seamen' : Scottish Church Ship Models and the Shipmaster's Societies of North East Scotland in the Late 17th Century / Meredith Greiling -- 10. Systematizing the Sea : Knowledge, Power and Maritime Sovereignty in Late Seventeenth-Century Science / Philippa Hellawell.
Online resource; title from PDF title page (EBSCO, viewed October 12, 2020).
Includes bibliographical references and index.
In English.
JSTOR
Keywords: Great Britain. -- Royal Navy -- History; Great Britain. -- Royal Navy; Great Britain -- History; Sea-power -- Great Britain -- History; Grande-Bretagne -- Histoire navale -- 16e siècle.; Grande-Bretagne -- Histoire; Puissance maritime -- Grande-Bretagne -- Histoire; British and Irish history; Early modern history: c 1450/1500 to c 1700.; Maritime history; HISTORY -- Maritime History & Piracy .; Sea-power; Great Britain; Maritime, Britain, Sea, early modern, culture; History